(untitled) (Baghdad Science Journal, 2005)
the chormanal some complement of barbus grypius is found to be 98 consisting of 22 melaccntricsomes it is probably a tetraploid species and more advanced than other speice haveing the same ehromosome under and belonging yo the genus barbus